Effects of acepromazine, xylazine and propofol on spinal reflexes in healthy dogs - Ali Sheykhbahaedinzade; Ali Asghar Sarchahi; Hossein Kazemi Mehrjerdi (Veterinary Medicine and Science)
Abstract Background In the neurological examination, it is crucial to identify the possible location of the lesion in order to determine the appropriate treatment process. In aggressive animals, chemical restraint may be necessary due to their non‐cooperative behaviour. However, sedatives may distort the results of examinations. Therefore, a drug should be found that has minimal impact on the examination results. Objectives To investigate the effects of acepromazine, xylazine, and propofol on spinal reflexes in healthy dogs. Methods In a randomized, blinded study, ten native adult mixed‐breed dogs were participated in three groups with a 1‐week washout period between each group. Before performing each step, the spinal reflexes were evaluated. Then, in the first group, acepromazine (0.05 mg/kg, IM), in the second group, xylazine (1 mg/kg, IM), and in the third group, propofol (3 mg/kg, IV for initial bolus and 0.1 mg/kg/min for maintenance) were injected for sedation. The spinal reflexes were reevaluated at maximum sedation and at 15, 30, and 45 min thereafter. Results Acepromazine increased the patellar reflex and decreased the panniculus reflex. Xylazine increased the cranial tibial reflex and decreased the panniculus reflex, while propofol decreased the withdrawal, and extensor carpi radialis reflexes, and suppressed the palpebral and gag reflexes. Conclusions The drugs used in the present study did not have a significant impact on the most important reflexes evaluated in neurological examinations. Among the drugs, acepromazine has the least effects compared to other drugs, making it a suitable choice for sedation.